Dairy development in the Caribbean region - Walmsley, Don (Technical Centre for Agricultural and Rural Cooperation, 1993)
This publication is a compiIation of the presentations,conclusions and recommendations given at a seminar held at Ocho Rios, Jamaica, 30 November-3 December 1992.